Study guide to "Preventive medical care in psychiatry" : a case approach - McCarron, Robert M. (American Psychiatric Association Publishing, 2017)
The newly published Guide employs a case-based approach designed to help readers master the most critically important material in the primary text. The guide's organization reflects the text's structure, allowing readers to use it concurrently, to check comprehension, or to test their knowledge after completing the text.